How supply chain architecture and product architecture impact firm performance: An empirical examination. Issue 1 (January 2019) - Saeed, Khawaja A.; Malhotra, Manoj K.; Abdinnour, Sue
Abstract: In order to enhance performance, manufacturing firms are building various capabilities and utilizing supply chain networks that are geographically dispersed around the globe. This study examines how decisions related to supply chain architecture and product architecture influence organizational competitiveness. Building on the co-specialization perspective, we evaluate the performance implications of product modularity and supply chain agility. While, product modularity constitutes a product configuration related to sourcing and assembling of products, supply chain agility is a supply chain configuration related to velocity (sensing, comprehending, and responding) and visibility (supplier network, internal operations, and external environment). Both the product and supply chain architectural decisions can impact performance, individually and in conjunction with each other. We empirically test the hypothesized relationships using data collected from 103 manufacturing firms. Results show that supply chain agility and product modularity directly enhance responsiveness and enable organizations to reduce cost. Furthermore, supply chain agility partially mediates the relationship between product modularity and both responsiveness and cost reduction. We elaborate on the key contributions of this study for both research and practice, discuss limitations, and also offer various avenues for further research. Highlights: How supply chain architecture and product architecture influence organizational competitiveness. Expanded conceptualization of supply chain agility to include comprehending as an additional dimension. Agile practices improve delivery performance and reduce costs, two outcomes often portrayed as competing objectives. Important to explore complementariness between agile practices and modular product architecture. Conceptualization of supply chain agility can be used by organizations to gauge areas of strength and areas that need improvement.